Attitudes towards counterfeits of luxury brands: the Singapore story - Teah, Min; Phau, Ian (University of Western Sydney, 2008)
The paper examines the factors that influence the attitudes of Singaporean consumers towards counterfeits of luxury brands. Data was collected using a self-administered questionnaire from 300 postgraduate students of a large university. Both social influence and price quality inference were found to significantly influence attitudes towards counterfeits of luxury brands. There is no significant relationship with brand consciousness, personal gratification, value consciousness, and brand prestige. Attitudes towards counterfeits of luxury brands were found to influence purchase intention. A research model is developed together with an agenda of seven hypotheses. The main contributions of the proposed research are also delineated.